Magnetovariational study over Lakshadweep Islands, southwestern continental margin of India - Subbarao, P. B. V.; Arora, B. R. (My University, 2007)
The Chagos-Laccadive Ridge (CLR) is a prominent aseismic topographic feature in the northern Indian Ocean. The evolution and origin of the CLR continues to be a subject of great debate. Geomagnetic depth sounding studies have been carried out in five different Lakshadweep Islands. Transfer functions, summering relationship between anomalous and normal components of transient geomagnetic variations, by virtue of their sensitivity to sub-surface electrical conductivity distribution facilitate to constrain the deep structure and thermal state of the CLR. The induction arrows over a wide range of periods indicates dominance of island effect. The residual induction arrows (obtained after accounting for the Island effect) suggest the concentration of anomalous induced currents in an elongated structure corresponding with track of the Reunion hotspot. Further, the thin sheet modelling of the residual induction arrows brings out a narrow belt of high-conductivity zone close to the eastern margin of the CLR. This is interpreted in terms of partial melt associated with the northward drifting of Indian plate over the Reunion mantle plume (65 Ma). The increase in the longitudinal conductance from north to south can be attributed to the degree of partial melting with younging of the age of volcanic intrusion to the south.
Keywords: Magnetovariational study; Chagos Laccadive Ridge (CLR); Lakshadweep Islands; Reunion hotspot; Induction arrows